The seasonal patterns of gibberellin-like substances in the buds, flowers and fruit of Prunus Salicina L. cv. Songold, as affected by a single autumnal foliar application of paclobutrazol - Huysamer, Marius (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1988.